Pengawetan dan Pemberian Nilai Tambah Produk Jamur Tiram Putih Menjadi Sate dan Bakso Jamur - Agus Sugianto; Anis Sholihah (University of Merdeka Malang, 2021)
The unsolved problem of mushroom farmers in Blayu village is post-harvest handling and adding value to mushroom fruit bodies, if the harvest is high, many farmers experience losses because they cannot store more than 7 days. The service was carried out in Blayu village, Wajak, Malang Regency, divided into six stages: (1). Program socialization to farmer groups; (2). Post-harvest technology extension; (3). Training and mentoring of mushroom fruit preservation technology, (4). Training and assistance in making mushroom-based fast food, (5) Procurement of infrastructure, (6) Monitoring, evaluation and reporting. The results of the service program can be concluded: 1). The mushroom farmers in the Guyub Makmur farmer group have mastered the technology of preserving white oyster mushrooms, reaching 90%; 2). Preservatives and ingredients and accessories, storage tools, tools for making mushroom meatballs and mushroom satay are available; 3). 100% of farmer groups can make satay and mushroom meatballs and start a business selling mushroom meatballs, the income of farmer groups increases between 55% - 65% compared to before; 4). An IPR has been produced entitled